Survey of Understanding Levels of Futsal Game Rules (Laws of The Game) on Futsal Extracurricular Participants - Labib Ramdhani; Hasan Basri (PARADIGMA : JURNAL ILMU PENGETAHUAN AGAMA, DAN BUDAYA, 2023)
This study aims to determine the level of understanding of the rules of the game of futsal (laws of the game) among students participating in futsal extracurricular activities for SMA/SMK in Rawalumbu District, Bekasi City. This research is a descriptive qualitative research. Data analysis techniques using quantitative descriptive presented in the form of a percentage. Based on the results of data analysis and discussion, it can be concluded that the level of understanding of the rules of the game of futsal (laws of the game) in futsal extracurricular participants throughout Rawalumbu District, Bekasi City in the "less" category is 0%, and "sufficient" is 0%. This means that there are no students participating in futsal extracurricular activities who have "low" and "sufficient" abilities towards understanding the rules of the game of futsal (laws of the game). While students participating in extracurricular futsal in the "very good" category were 23 respondents (38.33%) and "good" were 37 respondents (61.67%). This means that all student respondents participating in the futsal extracurricular activities for high schools/vocational schools in Rawalumbu District, Bekasi City have good knowledge of the rules of the game of futsal (laws of the game). Thus it was concluded that the level of understanding of the rules of the game of futsal (laws of the game) in the extracurricular participants in the futsal extracurricular SMA/SMK in Rawalumbu District, Bekasi City, was in the "good" category with an average score of 23.36.